Knowledge, Attitudes, and Perceptions Regarding the Future of Artificial Intelligence among Health-care Professionals - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2023)
Artificial intelligence (AI) systems have been extensively employed in a variety of fields including medicine. The present study aimed to describe Saudi Arabian health-care professionals’ knowledge, attitudes, and perceptions of the future of AI. Materials and Methods: The present study was a cross-sectional study that was carried out in November 2022 and included an online survey to describe Saudi Arabian health-care professionals’ knowledge, attitudes, and perceptions of the future of AI. Results: The survey was filled out by 174 health-care workers. About 87.9% of health-care professionals said they are familiar with AI and its uses. About 89.7% said that they would like to use a software/program that can be helpful in disease diagnosis and treatment. More than 97% of health-care workers agreed that AI has a future in the medical field and 93.1% of them agreed that AI will help them in making decisions. Conclusion: Health-care professionals are concerned about the possible effects of its widespread application in clinical practice. Attending lectures, conferences, and workshops is essential for enhancing health-care professionals’ knowledge and attitude regarding AI and reducing their conflict.